Firm Profitability And The Administration Of Working Capital: Delving Into A Case Of The Cement Sector Of Pakistan - Farhan Ullah; Farhan Ullah; Dr. Mustafa afeef (Journal of Business & Tourism, 2021)
This study endeavors to establish an association between the administration of working capital and firm returns in Pakistan’s cement sector. Ten companies listed in the cement industry of KSE 100 Index were taken from Pakistan Stock Exchange randomly. Financial data in secondary form was collected from the financial reports of cement firms of the country. The study employed return on assets as an explained variable and inventory turnover period in days, collection period in days, payment period, cash conversion cycle, sales in log, and liquidity ratios as explanatory variables while controlling for the influence offirm’s size and firm’s growth in terms of sales. It was found that the current ratio, log of sales, cash conversion cycle and inventory conversion period positively influenced the return of companies whereas size of the firm, collection period of receivables, payment period to creditors and the debt ratio of firms had a negative influence on it.